2021
DOI: 10.1038/s41574-021-00499-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of regulated necrosis in endocrine diseases

Abstract: The death of endocrine cells is involved in type 1 diabetes mellitus, autoimmunity, adrenopause and hypogonadotropism. Insights from research on basic cell death have revealed that most pathophysiologically important cell death is necrotic in nature, whereas regular metabolism is maintained by apoptosis programmes. Necrosis is defined as cell death by plasma membrane rupture, which allows the release of damage-associated molecular patterns that trigger an immune response referred to as necroinflammation. Regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 224 publications
(285 reference statements)
0
34
0
Order By: Relevance
“…It has become appreciated recently that necrotic cell death is not always accidental and can instead occur downstream of regulated signaling events. Such types of regulated necrosis are lytic forms of cell death that can drive inflammation and immune responses following plasma membrane rupture and the release of cellular cargo into the extracellular environment [250]. Given previous observations of the molecular mechanisms of β-cell death, ferroptosis and necroptosis appear to be two forms of regulated necrosis with potential relevance to diabetes pathogenesis [252,[259][260][261].…”
Section: β-Cell Regulated Necrosismentioning
confidence: 97%
See 2 more Smart Citations
“…It has become appreciated recently that necrotic cell death is not always accidental and can instead occur downstream of regulated signaling events. Such types of regulated necrosis are lytic forms of cell death that can drive inflammation and immune responses following plasma membrane rupture and the release of cellular cargo into the extracellular environment [250]. Given previous observations of the molecular mechanisms of β-cell death, ferroptosis and necroptosis appear to be two forms of regulated necrosis with potential relevance to diabetes pathogenesis [252,[259][260][261].…”
Section: β-Cell Regulated Necrosismentioning
confidence: 97%
“…The presence of certain morphological changes, such as cell shrinking, nuclear condensation, DNA fragmentation, exposure of phosphatidylserine on the plasma membrane, and membrane blebbing, can also be used to identify apoptosis [248,249]. Membrane blebs (also known as apoptotic bodies) encompass cellular content from apoptotic cells for phagocytosis by immune cells, thereby preventing release into the extracellular space and avoiding unwanted immune responses to this physiological process [250]. Thus, while apoptosis likely contributes to the loss of β cells in diabetes, it can also be regarded as a normal physiological process that is immunologically silent [251].…”
Section: Potential Future Advances In Understanding β-Cell Death In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis can be activated by inhibition of glutathione peroxidase 4 (GPX4) (the membrane repair enzyme) or the glutamate/cystine antiporter (xCT), whereas it can be inhibited by iron chelators, lipophilic antioxidants, polyunsaturated fatty acid phospholipids (PUFA-PLs), and lipid peroxidation inhibitors [ 9 , 10 ]. All these regulated necroses participate in the development of multiple diseases, including cardiocerebrovascular injury [ 11 ], neurological disease [ 12 ], ischemic stroke injury [ 4 , 13 ], digestive diseases [ 14 ], kidney diseases [ 15 17 ], liver diseases [ 18 ], endocrine diseases [ 19 ], hypertension [ 20 ], pulmonary disease [ 21 , 22 ], and cancer [ 7 , 23 , 24 ]. Moreover, it has also been implicated in the pathogenesis of corneal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated the critical regulatory role of pyroptosis in the tumor microenvironment (TME), which provides new therapeutic insights for cancer treatment [ 16 ]. Therefore, an in-depth study of pyroptosis may help understand its role in the occurrence and development of cancers including HCC and provide new ideas for the clinical prevention and treatment [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%